2015
DOI: 10.5772/60109
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Detection of Enantioselective Adsorption by Chiral Au Nanoparticles — Effects of Temperature, Wavelength and Size

Abstract: R-and S-propylene oxide (PO) have been shown to interact enantiospecifically with the chiral surfaces of Au nanoparticles (NPs) modified with D-or L-cysteine (cys). This enantiospecific interaction has been detected using optical polarimetry measurements made on solutions of the D-or L-cys modified Au (cys/Au) NPs during addition of racemic PO. The selective adsorption of one enantiomer of the PO onto the cys/Au NP surfaces results in a net rotation of light during addition of the racemic PO to the solution. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…4,5 Chiral metal nanoclusters have properties that make them attractive for applications in different domains like enantiomeric separation, enantioselective detection, asymmetric catalysis, pharmaceutical applications and others. [6][7][8][9][10][11] The chirality of metal nanoclusters can be probed by electronic circular dichroism (CD). 12,13 CD spectra are a sensitive probe of the size and structure of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Chiral metal nanoclusters have properties that make them attractive for applications in different domains like enantiomeric separation, enantioselective detection, asymmetric catalysis, pharmaceutical applications and others. [6][7][8][9][10][11] The chirality of metal nanoclusters can be probed by electronic circular dichroism (CD). 12,13 CD spectra are a sensitive probe of the size and structure of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…In order to chirally modify the THH-Au NPs, their surfaces were coated with D-or L-Cys by mixing 1 mL of the THH-Au NP solution with 4 mL of 0.050 M D-or L-Cys in deionized water [6][7][8] . The solution was sonicated for approximately 30 minutes and then allowed to sit for approximately one hour before making optical rotation measurements.…”
Section: Coating Of Thh-au Nps With D or L-cysteinementioning
confidence: 99%
“…Prior work has shown that simple chiral probe molecules such as R-and S-propylene oxide (PO) can be adsorbed enantioselectively onto the surfaces of Au NPs that have been chirally modified with either D-or L-cysteine (Cys) [6][7][8] . The work herein, advances prior accomplishments by using tetrahexahedral (THH, 24-sided) Au NPs exposing well-defined crystal planes and, more importantly, demonstrating that the methodology works with use of a known pharmaceutical, propranolol (PLL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, Au-NPs were either spherical or tetrahexahedral (24-sided) in shape. A systematic study has also been performed to understand the effects of temperature and of Au-NP size on enantiospecific adsorption from racemic PO [ 14 ]. These studies made use of optical polarimetry as a means of detecting enantioselective adsorption and used a model developed by us to analyze optical rotation measurements and quantify enantiospecific adsorption equilibrium constants.…”
Section: Introductionmentioning
confidence: 99%